Perlindungan pada Citra Motif Kain Songket dengan Teknik Watermarking Menggunakan RSA Encryption dan MSB Steganography - Gemuh Raharja RL, I Wayan Gede; Agus Sanjaya ER, Ngurah (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2024)
This research develops a watermarking steganography technique using the MSB method to protect songket cloth motifs. In the MSB-based steganography method for embedding watermarks in images, the MSB transformation is used to replace data bits in image segments with secret data bits. The embedded watermark functions as an identification mark that is difficult to remove or change without destroying the authenticity of the original motif. Accuracy testing using PSNR and MSE produced an average PSNR of 75.177 dB and MSE of 0.0018, which shows that this technique is effective in maintaining the authenticity and integrity of Songket cloth motifs.